A scientometric review of global research on sustainability and sustainable development - Olawumi, Timothy O.; Chan, Daniel W.M. (Journal of cleaner production, 2018)
The concept of sustainable development has gained worldwide attention in recent years which had enhanced its implementation. However, few studies have attempted to map the global research of sustainability. This study utilizes scientometric review of global trend and structure of sustainability research in 1991–2016 using techniques such as co-author, co-word, co-citation, clusters, and geospatial analyses. A total of 2094 bibliographic records from the Web of Science database were analyzed to generate the study's research power networks and geospatial map. The findings reveal an evolution of the research field from the definition of its concepts in the Brundtland Commission report to the recent development of models and sustainability indicators. The most significant contributions in sustainability research have originated primarily from the United States, China, United Kingdom and Canada. Also, existing studies in sustainability research focus mainly on subject categories of environmental sciences, green & sustainable science technology, civil engineering, and construction & building technology. Emerging trends in sustainability research were sustainable urban development, sustainability indicators, water management, environmental assessment, public policy, etc.; while the study generated 21 co-citation clusters. This study provides its readers with an extensive understanding of the salient research themes, trends and pattern of sustainability research worldwide. •Sustainability research is evolving and expanding to several frontiers.•This research reviewed 2096 bibliographic records from the Web of Science database.•Salient and emerging sustainability research trends and clusters were identified.•The findings are applicable to key stakeholders such as the government and organizations, researchers, among others.